Gambaran Ketepatan Terapi Obat Anti Epilepsi Sesuai Bentuk Bangkitan berdasarkan PERDOSSI di RSUD Al-Ihsan Bandung Tahun 2020 - Naufal Rafif Ji'aul Haq; M. Ahmad Djojosugito; Alya Tursina (UNISBA Press, 2022)
Abstract. Epilepsy has a high number of cases in the world and in Indonesia. Attacks are significantly reduced in number or severity with antiepileptic drugs. Guidelines on epilepsy including its treatment have been prepared by PERDOSSI following the developments of the International League Against Epilepsy. Following the guidelines will increase safety and efficacy, reduce the risk of drug interactions and side effects, including lowering the cost of treatment. The purpose of this study was to describe the accuracy of anti-epileptic drug therapy according to the form of seizure based on PERDOSSI at the Al-Ihsan Regional General Hospital (RSUD) Bandung in 2020. The research method was a descriptive study with a cross-sectional design and presented in tabulation and percentages. Data were taken from the medical records of outpatient epilepsy patients at the Al-Ihsan Hospital in Bandung for the period January - May 2020. Results: The accuracy of administering anti-epileptic drug therapy according to the form of seizure based on PERDOSSI in outpatient treatment at Al-Ihsan Hospital Bandung was 15 people (36.58 %) with a 95% confidence interval, which means that the accuracy of the proportion of samples representing the population is actually 21.8%-51.3%. The factors that are thought to influence this study are the availability of drugs, and the consideration of side effects of the drugs given. Further research needs to find anti-epileptic drugs according to PERDOSSI for unclassified seizure types. Abstrak. Epilepsi memiliki kasus yang tinggi di dunia dan Indonesia. Serangan berkurang dengan signifikan dalam jumlah atau tingkat keparahannya dengan obat anti epilepsi. Pedoman mengenai epilepsi termasuk pengobatannya telah disusun oleh PERDOSSI yang mengikuti perkembangan dari International League Against Epilepsy. Mengikuti pedoman akan meningkatkan keamanan dan efikasi, menurunkan resiko interaksi obat dan efek samping, termasuk menurunkan biaya dari pengobatan. Tujuan penelitian ini untuk mengetahui gambaran ketepatan terapi obat anti epilepsi sesuai bentuk bangkitan berdasarkan PERDOSSI di Rumah Sakit Umum Daerah (RSUD) Al-Ihsan Bandung Tahun 2020. Metode penelitian merupakan studi deskriptif dengan desain potong lintang dan disajikan dalam tabulasi dan persentase. Data diambil melalui rekam medik pasien epilepsi rawat jalan di RSUD Al-Ihsan Bandung periode Januari - Mei tahun 2020. Hasil: Ketepatan pemberian terapi obat anti epilepsi sesuai bentuk bangkitan berdasarkan PERDOSSI di rawat jalan RSUD Al-Ihsan Bandung sebanyak 15 orang (36,58%) dengan interval kepercayaan 95% yang bermakna keakuratan proporsi sampel mewakili populasi sesungguhnya bernilai 21,8%-51,3%. Faktor yang diduga mempengaruhi pada penelitian ini yaitu ketersediaan obat, dan pertimbangan efek samping obat yang diberikan. Penelitian lanjutan perlu mencari obat anti epilepsi sesuai PERDOSSI untuk tipe bangkitan yang tidak terklasifikasikan.